ANALYSIS RELAY PERFORMANCE IN MOTOR DC CONTROL FOR DISTANCE DETECTION OBJECT - Riza Arif Pratama; Sahid Bayu Setiajit; Herdias Raffa Dearly; Sulcan Izul Zamharir (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2026)
DC motor control system needs to have consistent rotation settings so that safety indicators are more stable. Negligence in operation needs to be monitored to reduce incidents in nearest zone of DC motor installation. Research on relay response to distances below safe was carried out by examining three parameters, namely distance accuracy, relay response, and monitoring indicators with experimental testing. Results of study have produced a distance accuracy of 99.21% which indicates good human detection. The relay response in controlling DC motor has been able to work according to the zone that has been determined in Arduino programming. Monitoring indicators are in accordance with the LCD display and audible warnings by buzzer if humans enter in danger zone DC motor area. Determination of location of the active sensor is in accordance with installation area so that it can be monitored correctly.